Does work stress & workplace incivility influence Employee Turnover Intentions? Mediating Role of Work-family Conflict - Mehmood, Shahid; Aziz, Azelin; Husin, Nurul Sharniza (Innovation Journal of Social Sciences and Economic Review, 2023)
The purpose of this study was to assess the impact of work stress and workplace incivility on turnover intention and work-family conflict. As well as the role of work-family conflict in mediating the relationship between work stress, workplace incivility, and turnover intention. The data was collected by distributing 573 questionnaires to nurses working in the healthcare sector in Punjab, Pakistan. The SPSS (23) statistical package was used to analyze the data, and the model was evaluated using partial least squares (Smart PLS 3.3). The findings showed that workplace stress and incivility had a direct positive effect on turnover intention. Additionally, there was a positive relationship between work stress and workplace incivility, as well as a negative relationship between work-family conflict and workplace incivility. Work-family conflict positively mediates the relationship between work stress and turnover intention, but there is no such relationship between workplace incivility and turnover intention. The results provide empirical evidence that work stress, and workplace incivility, are positively related to intent to leave the organization. Furthermore, the conceptual framework of this study can be a guide for future research on turnover intention. This study is unique, as it is the first study conducted on work stress and workplace incivility in a hospitality setting. The study responded to scholarly calls made to enrich the literature pertaining to work stress, workplace incivility, and its outcomes.